2011
DOI: 10.1007/s11255-010-9896-3
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from a fatal case of mercury intoxication

Abstract: Despite the tragic outcome, on review of case literature, we believe this case provides valuable lessons concerning the use of DMSA and DMPS to treat mercury toxicity, particularly with regard to the combined use of chelation agents and hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…It reduces the blood level of mercury and relieves clinical symptoms. [ 10 , 20 ] DMPS and DMSA are the major chelating agents used in clinical settings. However, mercury was secreted from the body so slowly, at a speed of 1 mg per day through kidney, that chelation therapy may take years, even whole life, to clear the toxicant completely.…”
Section: Discussionmentioning
confidence: 99%
“…It reduces the blood level of mercury and relieves clinical symptoms. [ 10 , 20 ] DMPS and DMSA are the major chelating agents used in clinical settings. However, mercury was secreted from the body so slowly, at a speed of 1 mg per day through kidney, that chelation therapy may take years, even whole life, to clear the toxicant completely.…”
Section: Discussionmentioning
confidence: 99%
“…Este cuadro clínico se denomina eretismo mercurial. La intoxicación crónica puede cursar con alteraciones renales que van desde la proteinuria aislada al síndrome nefrótico, en el contexto de nefropatía membranosa secundaria a nefritis por inmunocomplejos (depósitos de Ig G1 y de C 3 ) [8][9][10] .…”
Section: Discussionunclassified
“…Davey and Benson [15] and Alhamad et al [5] reported metal dense deposits in the heart following intravenous injection of metallic mercury or inhalation of vaporized mercury. Intra-arterial injection can cause ischemia and/or gangrene secondary to embolisation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, haemodialysis and plasma exchange are only indicated if renal failure occurs combined with anuria [5,13]. Nevertheless, Yoshida et al [13] suggested that renal damages due to acute mercury poisoning may not be permanent.…”
Section: Discussionmentioning
confidence: 99%